Observations of Bedform Migration and Bedload Sediment Transport in Combined Wave‐Current Flows. Issue 7 (5th July 2019) - Wengrove, M. E.; Foster, D. L.; Lippmann, T. C.; de Schipper, M. A.; Calantoni, J.
Abstract: Bedload transport is an important mechanism for sediment flux in the nearshore. Yet few studies examine the relationship between bedform evolution and net sediment transport. Our work contributes concurrent observations of bedform mobility and bedload transport in response to wave dominant, current dominant, and combined wave‐current flows in the nearshore. Bedload sediment flux from migrating bedforms during combined wave‐current conditions accounted for at least 20% more bedload transport when compared with wave dominant flows and at least 80% more than current‐dominant flows. Bedforms were observed to transport the most sediment during periods with strong currents, with high‐energy skewed waves, and while bedform orientation and transport direction were aligned. Regardless of flow type, bedform migration rates were directly proportional to the total kinetic energy contained in the flow field. Eleven bedload transport models formulated to be used in combined flows (both shear and energetics based) were compared with sediment flux estimated from measured bedform migration. An energetics based sediment transport model was most representative for our data. Key Points: The total kinetic energy in the flow field and the bedform migration rate are directly proportional Sediment flux in combined wave currents was found to be greater than in wave dominant flows with comparable kinetic energy Data and comparison with bedload sediment flux models shows that energetics may be most representative of system physics